Aktivitas Hedging dengan Instrumen Derivatif dan Nilai Perusahaan - Pramana, A.A. Gede Indra; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 30 No 9 (2020)DO - 10.24843/EJA.2020.v30.i09.p01, 2020)
The increase of exchange rate fluctuation pushes firms to form an optimal risk management. Risk management, especially in the form of hedging activity with derivative instrument has moved from pure risk mitigation to value creator for firm. The purpose of this study is to determine the effect of hedging activity with derivative instrument on firm value. This study was conducted on nonfinancial firms listed on Indonesia Stock Exchange during the period of 2013-2017. Sample of 183 firms was obtained through nonprobability sampling technique with purposive sampling method. Data collection was done with nonparticipant observation. Analysis technique used in this study is multiple linear regression analysis. Based on analysis result, hedging activity with derivative instrument has a positive effect on firm value. Keywords: Hedging; Derivative Instrument; Risk Management; Firm Value.